Cultural adaptation and validation of the attitudes towards alcohol scale for health professionals in Portugal - Seabra, Paulo; Robalo Nunes, Inês; Henriques Silva, Vanessa Alexandra; Valentim, Olga; Guedes De Pinho, Lara; Moutinho, Lidia; VARGAS, D; Curado, Maria Alice dos Santos (Springer, 2023)
We aimed to conduct an adaptation and validation of the Attitudes towards Alcohol, Alcoholism and Individuals with Alcohol Use Disorders Scale (EAFAA) which set to address the main groups of attitudes. It is composed in its original version by 50 items, divided into 4 factors: (1) work and interpersonal relationships with patients with alcohol consumption disorders; (2) the person with alcohol consumption disorders; (3) alcoholism (aetiology) and (4) alcoholic beverages and their use. The cultural adaptation from Brazilian to European Portuguese changes 22 items and the designation of one factor. The content validity index scale was 0.96. The psychometric properties were analysed through a cross-sectional study, with a convenience sample of 500 health professionals and students. The confirmatory factor analysis model with the same four (4) original factors, led to the elimination of 9 items. The scale revealed Cronbach’s alpha of 0.801. Empirical adjustment indices were satisfactory with Minimum Discrepancy Function by Degrees of Freedom divided (CMIN) ( X2/gl) = 3.91; p < 0001, RMSEA = 0.076 and the goodness of fit index (GFI) with 0.8. Relative indices values were normal fit index (NFI) = 0.6, comparative fit index (CFI) = 0.7 and Tucker-Lewis index
Keywords: Transtornos relacionados ao álcool; Enfermeiro-paciente relações; Conhecimento, atitudes e práticas em saúde; Psicometria; Profissionais de saúde